Change of direction density: a novel consideration of consecutive changes of direction in elite youth soccer - Morgan, O. J.; Drust, B.; Ade, J. D.; Robinson, M. A. (The Journal of Strength and Conditioning Research, 2025)
This study aimed to characterize change of directions (CODs) based on density (number of CODs within 10 seconds), locomotor activity (walk, jog, stride, and sprint), and movement direction pre- and post-COD (forwards, sideways, and backwards), relative to playing position. In total, 24 elite male English Premier League academy soccer players (mean ± SD; age: 19.0 ± 1.9 years, height: 179.9 ± 7.0 cm and body mass: 71.9 ± 6.4 kg) were individually filmed during 10 competitive matches. In total, 7,399 CODs were observed. Level of significance was p = 0.05. An average of 84 ± 23 multiple COD events per player, per game occurred with no significant difference between position. Six CODs within 10 seconds were the average maximum density across positions (1.4 ± 1.2), with 9 CODs within 10 seconds being the maximum observed. Overall, 94% of multiple COD events were 2, 3, and 4 CODs within 10 seconds collectively, and were each performed significantly more than all other density categories (5-9 CODs in 10 seconds) (p < 0.001). Jogging and striding pre- and post-COD were the most common locomotor activities (p < 0.05). Change of directions were rarely surrounded by sprinting (1.4 ± 1.4) with <1% of total CODs with a sprint (pre and post) with approximately half of CODs (53%) occurring in a forward movement pre- and post-COD. Change of directions seem to be performed as multiple events, in multiple directions, at mostly submaximal locomotor activities, with some positional differences for movement direction and locomotor activity pre- and post-COD. These data provide valuable guidance for practitioners for testing, conditioning, and rehabilitating soccer players.